Subjective and objective indices in determining stretching effect. - Shinichi Daikuya; Yumi Okayama (PLoS ONE)
Stretching is widely used in clinical settings to maintain and enhance physical functions. Despite numerous studies investigating its effects, subjective evaluations by therapists remain common, lacking objective assessment criteria. This study aims to bridge this gap by correlating objective measures with subjective evaluations by therapists and patients. The hypotheses are: (1) significant correlation between objective measures and subjective assessments, (2) consistency in therapist judgments, and (3) identification of objective criteria. This research aims to formalize clinical knowledge and enhance stretching interventions' applicability. Sixteen physiotherapists participated, with varying clinical experience. Straight leg raising stretching was performed on a simulated patient. Objective measures included joint angle, electromyography, and posterior thigh stiffness. Subjective evaluations were made by therapists and simulated patient using numerical rating scales. Therapists' ratings correlated positively with straight leg raising angle change and stretching duration. Simulated patient's ratings correlated positively with an integral electromyographic values of semitendinosus muscle activity but negatively with joint angle change. Regression analysis did not yield significant predictive models. Subjective evaluations may deviate from objective outcomes, highlighting the need for a better understanding of their relationship. Physiotherapists detected small joint angle improvements subjectively, but no objective predictor of this change was found. Patients' subjective evaluations did not align with objective outcomes. This suggests therapists' evaluations may be more accurate. Additional investigation into subjective evaluation criteria is warranted. Therapists should be cautious in relying solely on patient feedback, emphasizing the need for objective assessment in clinical practice.